Предпосылки учета структурных особенностей простых чисел при решении задачи факторизации в контексте построения атаки на шифротекст, который зашифрован асимметричным методом шифрования - Мохор, В.В.; Жилин, А.В. (Моделювання та інформаційні технології, 2009)
Pre-conditions of account of structural features of prime numbers are
grounded at the decision of task of factorization. It is assumed that by offered approach it is possible to organize an attack on shifrotekst, calculable complication of which will be below exponential.